Co-cultivation of Chaetoceros calcitrans and Arthrospira platensis growing on palm oil mill effluent under outdoor condition to produce fucoxanthin and c-phycocyanin. (January 2023) - Nur, Muhamad Maulana Azimatun; Djarot, Ira Nurhayati; Sasongko, Nugroho Adi; Putra, Agusta Samodra; Hadiyanto,
Abstract: Fucoxanthin from microalgae is promising since the productivity is higher compared to macroalgae. However, dynamic environmental and nutritional factors in large scale and outdoor condition still limiting the production. This research investigated co-cultivation of Chaetoceros calcitrans and Arthrospira platensis growing under outdoor condition and evaluated the pigment production when using palm oil mill effluent (POME) as medium growth. Results showed that co-cultivation strategy produced abundant biomass when growing up to 30 PSU salinity. The addition of POME to cultivation medium reduced fucoxanthin production, while C-phycocyanin (C-PC) production could be maintained. Mixed culture produced 27 mg/L C-PC and 5.4 mg/L fucoxanthin by using synthetic medium. The optimal condition for co-cultivation was 33% POME, 100 mg/L urea, and 17 PSU salinity to produce 1.7 mg/L fucoxanthin and 25 mg/L C-PC. Highlights: Co-cultivation strategy enhanced biomass production of mixed culture C. calcitrans and A. platensis. Salinity significantly influenced biomass and pigment production. POME has positive effect on C-PC production. Fucoxanthin production was influenced by the interaction of salinity and urea. The lowest nutritional cost was found when POME fraction was used as medium growth.